Bahasa Bugis dan Penulisan Tafsir di Sulawesi Selatan - Muhammad Yusuf (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
Bugis language is one of the local languages ​​in Indonesia, particularly in South Sulawesi. Bugis language has its own script called Lontarak. Lontarak is a classic text that illustrates the lives of people in the past. There are three Lontarak are found in South Sulawesi, which classic Lontarak, Attoriolong, and Pau-Pau Rikadong. All three contain different content. In the midst of the threat of extinction due to the influence of globalization, then Muslims in South Sulawesi, especially Bugis language seeks to maintain the tradition by writing the Qur'an in the Bugis language interpretation using Lontarak script. It is also an attempt by Bugis scholars of South Sulawesi to collaborate between Islam and the treasures of wisdom.